Development of IoT-Based E-ticket Selling and Management System with QR code Scanner (Tickets.now) - Han Jie, Tan; Nayef Abdulwahab Mohammed Alduais, (Applied Information Technology And Computer Science, 2023)
Tickets.now is an e-ticket selling and management system with QR code scanner that designed to help any university students in Malaysia that would like to sell their event tickets easily. The main reason this system to be develop is because most of the university students in Malaysia faced a problem when selling their events ticket. The only way for them to sell the tickets is by using Google Form and any messaging application. This system lets the users able to register as organizer to sell the tickets of their events or as a customer which able to buy the tickets of the event from it. The significance of this project is to facilitate businesses’ usage of the internet for marketing purposes by making it more straightforward for them to do so.